Penerapan Strategi Pembelajaran Kontekstual Berbasis Deep Learning untuk Meningkatkan Kemampuan Siswa SMK Profita Kota Bandung dalam Menganalisis Teks Negosiasi - Yulia Herliani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to test the effectiveness of deep learning-based contextual learning strategies in improving the ability of SMK Profta Bandung students to analyze negotiation texts. Deep learning-based learning focuses on deep understanding, active student engagement, and the development of critical thinking skills in real-life relevant learning contexts. The research method used is Classroom Action Research (PTK) which involves two cycles, with the stages of planning, implementation, observation, and reflection. The subject of the study was grade X AKL students of SMK Profita Bandung with a total of 30 students. Data was collected through text analysis tests, observation of student activities, and interviews. The results of the study show that the application of deep learning-based contextual learning strategies is able to significantly improve students' understanding of the structure and content of negotiation texts. In the first cycle, the average student score reached 72, increasing to 85 in the second cycle. In addition, student involvement in learning also increased, indicated by active participation in discussions and collaborative task completion. This study concludes that the deep learning-based contextual learning approach is effective in improving the negotiation text analysis ability of vocational school students. This approach also builds critical thinking skills and the relevance of learning to students' real-life experiences.